2011
DOI: 10.1260/1369-4332.14.4.673
|View full text |Cite
|
Sign up to set email alerts
|

Novel Steel-Concrete-Steel Sandwich Composite Plates Subject to Impact and Blast Load

Abstract: This paper investigates the structural performance of steel-concrete-steel (SCS) sandwich composite system subject to impact and blast load. Novel J-hook shear connector was invented to prevent the separation of face plates from the concrete core. SCS sandwich specimens subject to 100 kg TNT blast a 5 m standoff distance were tested. The test results are reported and the factors affecting the blast resistance of SCS sandwich structures are discussed. Finite element analysis was carried out and the numerical re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
20
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 92 publications
(20 citation statements)
references
References 5 publications
0
20
0
Order By: Relevance
“…To overcome this disadvantage and develop slim deck for offshore constructions, J-hook connectors were developed by Liew et al [6] as shown in Figure 1 (d). From the previous studies, sandwich structure with J-hook connectors exhibited excellent performances under impact, blast, and fatigue loadings [7,8]. This type of structure has great potential for applications in hulls of cargo tank, bridge decks, offshore decks, shear walls, and protective structures as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 91%
“…To overcome this disadvantage and develop slim deck for offshore constructions, J-hook connectors were developed by Liew et al [6] as shown in Figure 1 (d). From the previous studies, sandwich structure with J-hook connectors exhibited excellent performances under impact, blast, and fatigue loadings [7,8]. This type of structure has great potential for applications in hulls of cargo tank, bridge decks, offshore decks, shear walls, and protective structures as shown in Figure 2.…”
Section: Introductionmentioning
confidence: 91%
“…Thanks to the high performance of steel-concrete composite structures, steel-concrete-steel (SCS) sandwich composite structure that takes advantages of both concrete compression performance and steel tension performance is a good alternative in the civil and offshore domain due to its excellent cost-strength performance (Marshall et al, 2010;Liew and Wang, 2011). The SCS sandwich composite exhibits significant structural and economic advantages over the conventional reinforced concrete structures in terms of higher flexural stiffness and high energy absorption capacity to withstand extreme environmental and accidental loads.…”
Section: Introductionmentioning
confidence: 99%
“…The blast loading is an impulsive loading which has extremely high pressure and short duration. The field explosive detonation is a conventional method to generate the blast loading [9][10][11][12][13][14]. However, the disadvantages of this method are that it is generally quite expensive and a long planning time is also needed.…”
Section: Introductionmentioning
confidence: 99%